EDUCAÇÃO, MUSEUS E CIBERCULTURA - Carvalho, Felipe; Santos, Edmea; Pimentel, Mariano; Santos, Rosemary dos (Revista Docência e Cibercultura, 2022)
v. 6, n. 4 (2022) - EDUCAÇÃO MUSEAL E A PANDEMIA DE COVID-19